An Anthology of Scottish women poets - Kerrigan, Catherine (Edinburgh University Press, 1991)
"More than one hundred poets are brought together in this unique anthology, encompassing work from the Middle Ages to the present day in Gaelic, Scots and English. The introduction provides the background and context to the different traditions in Scotland including the oral/ballad, Gaelic bardic and modern tradition and attempts to identify recurrent themes"--Publisher